Basal-Like Cell-Conditioned Medium Exerts Anti-Fibrotic Effects In Vitro and In Vivo - Khan, Petra; Fytianos, Kleanthis; Blumer, Sabrina; Roux, Julien; Gazdhar, Amiq; Savic, Spasenija; Knudsen, Lars; Jonigk, Danny; Kuehnel, Mark P.; Mykoniati, Sofia; Tamm, Michael; Geiser, Thomas; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
In idiopathic pulmonary fibrosis (IPF), basal-like cells are atypically present in the alveolar region, where they may affect adjacent stromal cells by paracrine mechanisms. We here aimed to confirm the presence of basal-like cells in peripheral IPF lung tissue in vivo, to culture and characterize the cells in vitro, and to investigate their paracrine effects on IPF fibroblasts in vitro and in bleomycin-injured rats in vivo. Basal-like cells are mainly localized in areas of pathological bronchiolization or honeycomb cysts in peripheral IPF lung tissue. Single-cell RNA sequencing (scRNA-seq) demonstrated an overall homogeneity, the expression of the basal cell markers cytokeratin KRT5 and KRT17, and close transcriptomic similarities to basal cells in the majority of cells cultured in vitro. Basal-like cells secreted significant levels of prostaglandin E2 (PGE2), and their conditioned medium (CM) inhibited alpha-smooth muscle actin (α-SMA) and collagen 1A1 (Col1A1) and upregulated matrix metalloproteinase-1 (MMP-1) and hepatocyte growth factor (HGF) by IPF fibroblasts in vitro. The instillation of CM in bleomycin-injured rat lungs resulted in reduced collagen content, improved lung architecture, and reduced α-SMA-positive cells. Our data suggested that basal-like cells may limit aberrant fibroblast activation and differentiation in IPF through paracrine mechanisms.